Smart farming for sustainable rice production: an insight into applications, challenges and future prospects - Hashim, Norhashila; Ali, Maimunah Mohd; Mahadi, Muhammad Razif; Abdullah, Ahmad Fikri; Wayayok, Aimrun; Mohd Kassim, Muhamad Saufi; Jamaluddin, Askiah (Elsevier, 2024)
Rice has a huge impact on socio-economic growth, and ensuring its sustainability and optimal utilization is vital. This review provides an insight into the role of smart farming in enhancing rice productivity. The applications of smart farming in rice production including yield estimation, smart irrigation systems, monitoring disease and growth, and predicting rice quality and classifications are highlighted. The challenges of smart farming in sustainable rice production to enhance the understanding of researchers, policymakers, and stakeholders are discussed. Numerous efforts have been exerted to combat the issues in rice production in order to promote rice sector development. The effective implementation of smart farming in rice production has been facilitated by various technical advancements, particularly the integration of the Internet of Things and artificial intelligence. The future prospects of smart farming in transforming existing rice production practices are also elucidated. Through the utilization of smart farming, the rice industry can attain sustainable and resilient production systems that could mitigate environmental impact and safeguard food security. Thus, the rice industry holds a bright future in transforming current rice production practices into a new outlook in rice smart farming development.